Unraveling the Multilevel Dynamics of Water, Sanitation, and Child Anthropometry in Indonesia - Rifa Kirana; Ahmad Komarulzaman (Makara Journal of Health Research)
Background: Anthropometrics, reflecting nutritional status, growth, and development, are crucial elements that can predict a person’s health and well-being. However, low anthropometric measures among children under 5 years remain a significant issue in Indonesia, often influenced by various factors at the household and community levels. Access to clean water and adequate sanitation has been identified as major determinants of these adverse health outcomes. This study analyzes the relationship between anthropometric measures and access to water and sanitation at household and community levels using a multilevel analysis approach.